SMYD3 promoter hypomethylation is associated with the risk of colorectal cancer. (4th July 2018) - Li, Bin; Pan, Ranran; Zhou, Cong; Dai, Jie; Mao, Yiyi; Chen, Min; Huang, Tianyi; Ying, Xiuru; Hu, Haochang; Zhao, Jun; Zhang, Wei; Duan, Shiwei
Aim: SMYD3 encodes histone lysine methyltransferase. The goal of our study was to investigate the association between SMYD3 methylation and colorectal cancer (CRC).Materials & methods: SMYD3 methylation was measured by quantitative methylation-specific PCR method in 117 pairs of CRC tumor and para-tumor tissues.Results: Significantly lower SMYD3 methylation was observed in CRC tumor tissues than para-tumor tissues (p = 0.002). Further subgroup analysis by clinical features showed that significantly lower SMYD3 methylation were only observed in the CRC patients with tumors of moderately and well differentiation, positive lymph node metastasis, and stage III + IV.Conclusion: Our work reported for the first time that SMYD3 promoter hypomethylation was associated with CRC. Graphical Abstract: